Chinese (Taiwan) Yearbook of International Law and Affairs. Volume 35 (2017) - Ma, Ying-jeou 1950- (Brill Nijhoff, 2018)
Intro -- Chinese (Taiwan) Yearbook of International Law and Affairs -- Copyright -- Contents -- Preface -- Essay -- Some Personal Reflections about Getting Started as an International Lawyer -- Articles -- Breaking the Silence of the Executive: The Residual Role of the Common Law Courts in the Determination of Statehood -- Sovereignty Over Dokdo as Interpreted and Evaluated from the Korean-Japanese Exchanges of Notes Verbales (1952-1965) -- Roles and Functions of Transitional Justice Mechanisms in the Asia-Pacific Region in the Development of International Law -- Third Parties and Insular Features After the South China Sea Arbitration -- Recognition" of Governments by International Organizations - The Example of the UN General Assembly and Asian States -- Special Report -- Coming "Inside": An Analysis of Visa Waiver Privileges for Domiciled ROC (Taiwan) Citizens with Reference to the United States -- Contemporary Practice and Judicial Decisions of the Republic of China (Taiwan) Relating to International Law, 2017 -- Explanatory Note -- I International Law in General -- Foreign Policy Report, 9th Congress of the Legislative Yuan, 3rd Session (March 6, 2017) -- President Tsai's Remarks at 2017 Asia-Pacific Security Dialogue -- Foreign Policy Report, 9th Congress of the Legislative Yuan, 4th Session (October 2, 2017) -- II Subjects of International Law -- III International Organizations -- Republic of China (Taiwan) and Intergovernmental Organizations -- MOFA Expresses Deep Regret and Dissatisfaction that Taiwan Not Yet Invited to WHA -- Republic of China (Taiwan) Rejects WHO Characterization of Its Participation in World Health Assembly and Expresses Its Strong Dissatisfaction to WHO Secretariat -- ROC Government's Position on Mainland Chinese Interference with Taiwan's Participation in WHA.